All‐Polymer Solar Cells Based on a Conjugated Polymer Containing Siloxane‐Functionalized Side Chains with Efficiency over 10%. Issue 47 (7th November 2017) - Fan, Baobing; Ying, Lei; Zhu, Peng; Pan, Feilong; Liu, Feng; Chen, Junwu; Huang, Fei; Cao, Yong
Abstract: A novel wide‐bandgap conjugated copolymer based on an imide‐functionalized benzotriazole building block containing a siloxane‐terminated side‐chain is developed. This copolymer is successfully used to fabricate highly efficient all‐polymer solar cells (all‐PSCs) processed at room temperature with the green‐solvent 2‐methyl‐tetrahydrofuran. When paired with a naphthalene diimide‐based polymer electron‐acceptor, the all‐PSC exhibits a maximum power conversion efficiency (PCE) of 10.1%, which is the highest value so far reported for an all‐PSC. Of particular interest is that the PCE remains 9.4% after thermal annealing at 80 °C for 24 h. The resulting high efficiency is attributed to a combination of high and balanced bulky charge carrier mobility, favorable face‐on orientation, and high crystallinity. These observations indicate that the resulting copolymer can be a promising candidate toward high‐performance all‐PSCs for practical applications. Abstract : A novel wide‐bandgap conjugated copolymer PTzBI‐Si based on an imide‐functionalized benzotriazole unit containing a siloxane‐terminated side‐chain is developed and used to fabricate all‐polymer solar cells (all‐PSCs). When processed with a green solvent 2‐methyl‐tetrahydrofuran, the all‐PSC exhibits a power conversion efficiency of 10.1%, which represents the highest efficiency ever reported for all‐PSCs.